THE INFLUENCE OF FINANCIAL PERFORMANCE AND NON FINANCIAL PERFORMANCE ON ISLAMIC CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: EVIDENCE FROM THE ISLAMIC BANKS IN INDONESIA - Siswanti, Indra (Accounting Department,, 2018)
The purpose of this study is to examine the influence of Financial Performance and Non Financial Performance on Islamic Social Responsibility Disclosure of the Islamic Banks in Indonesia. The sample used is 5 banks. The data in this study are secondary data, consists of annual reports of the Islamic banks for the periods of 2010 to 2017.Â The analysis technique used is panel data regression. The results of fixed effect model state that duties and responsibilities of sharia supervisory board, compliance sharia principles have a significant influence on Islamic Corporate Social Responsibility disclosure, where as financial performance does not influence on Â Islamic Corporate Social Responsibility disclosure.Â Keywords: Corporate Social Responsibility, Social Islamic Reporting, Financial Performance, and Islamic Corporate Social Responsibility Disclosure